Uji Kinerja Motor Bakar Empat Langkah Satu Silinder Dengan Variasi Tinggi Bukaan Katup Pada Sudut Pengapian Sepuluh Derajat Sebelum TMA Dengan Bahan Bakar Pertamax Plus - Jhoni Oberton; Azridjal Aziz (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Factors that also affect performance and reduce exhaust gas emissions are fuel quality combustion in the combustion chamber. One of the parameters that influence is the amount of supply of combustion air into the combustion chamber. Where this supply is governed by the camshaft mechanism through open-close of the intake valve and the exhaust valve. The purpose of this study is to determine the effect of reduction of lift camshaft on engine performance. The investigation was conducted on a Yamaha jupiter Z1 single-cylinder, four-stroke, spark ignition engine. The experiments were performed by varying the reduction of lift camshaft, with camshaft standard (CAM STD), camshaft condition 1 with reduction of lift camshaft 0.5 mm (CAM 1), camshaft condition 2 with reduction of lift camshaft 0.10 mm (CAM 2) and camshaft condition 3 with reduction of lift camshaft 0.15 mm (CAM 3) and speed of the engine (2000 rpm, 3000 rpm and 4000 rpm). As a result, the maximum effective braking power was on CAM STD, at the engine speed of 3000 rpm that was 535.072 Watt, minimum SFC (Specific Fuel Consumption) was on CAM 2, at the engine speed 3000 rpm that was 1.54 x 10-7 kg/J and the thermal of maximum braking efficiency was on the CAM 2, at the engine speed of 3000 rpm equal to 14.129%.Keywords: Performance, Internal Combustion Engine, Camshaft